2012
DOI: 10.1007/s00436-012-2857-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sublethal exposure to temephos and propoxur on reproductive fitness and its influence on circadian rhythms of pupation and adult emergence in Anopheles stephensi Liston—a malaria vector

Abstract: The present study was undertaken to investigate the effects of organophosphate and carbamate insecticides namely, temephos and propoxur respectively, on the life history of Anopheles stephensi Liston (Culicidae) under laboratory conditions. The late third instar larvae of the mosquito were exposed to sublethal concentrations of temephos and propoxur at LC(10), LC(30) and LC(50), respectively, and adult survivors were evaluated for fitness parameters. Sublethal effects were also evaluated in subsequent generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 15 publications
3
26
0
Order By: Relevance
“…Indeed it was reported that when exposed to insecticides containing temephos and propoxur, Anopheles stephensi females produced less viable eggs (Sanil and Shetty, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed it was reported that when exposed to insecticides containing temephos and propoxur, Anopheles stephensi females produced less viable eggs (Sanil and Shetty, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Insecticides have morphological effect on the reproductive organs of insects and effects on the reproductive capability is based on the mosquito response to the insecticides, inherent toxicity and mosquito species (Zin and Shetty, 2008). Application of insecticides resulted in the decreasing of the population, either by killing the susceptible strains and/or by decreasing the reproductive ability of the resistant strains (Sanil and Shetty, 2012). Anacardiaceae plants used in this study contain various compounds such as alkaloids, coumarins, saponins, tannins, reducing sugars, avonones, triterpenoids and steroids (Bbosa et al, 2007;Elumalai et al, 2012), which are previously reported for antifeedant, acute toxicity, repellent, fumigant and inhibiting reproduction of many insect species (Cox, 2004;Kubo, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…The reduction in the number of offspring of the toxic compounds is due to the change in behavior for mate positioning and oviposition which affecting the egg fertilization, ovulation and sperm motility (Ali et al, 2006). Having less fertile adults treated with toxic compounds will resulted in less fertile or unfertilized eggs, also will reduce the percentage of larval emergence (Sanil and Shetty, 2012). Sublethal effects on egg hatchability at higher doses and delayed on larval development are strongly reported for malaria and dengue vectors exposed to the methanolic extracts of Calotropis procure F. Aiton (Ramos et al, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 2 more Smart Citations